PENGARUH BAURAN PEMASARAN TERHADAP KEPUASAN PELANGGAN (Studi Pada Oli Sepada Motor Merek Agip di Toko Berkah Jaya Motor Garut) - Robby Rahman; Ramayani Yusuf; Rohimat Nur Hasan (Universitas Haji Sumatera Utara, 2023)
The research entitled The Effect of Marketing Mix on Customer Satisfaction in Agip Brand Motorcycle Oil at Berkah Jaya Motor Garut Shop is the result of a quantitative study that aims to answer questions about the effect of various Marketing Mix on Customer Satisfaction at Berkah Jaya Motor Garut Shop. The research methodology used is quantitative research using survey methods. sampling technique using google form with 100 respondents. data collection technique used a questionnaire which was processed using IBM SPSS 26. Data analysis used multiple linear regression. The results showed that the marketing mix had a partial effect on customer satisfaction